Evaluvation of Pongamia Oil Soap Against Major - Sajay S (Department of Agricultural Entomology, 2019)
The study entitled ‘Evaluation of pongamia oil soap against major pests of vegtable cowpea, Vigna unguiculata subsp. sesquipedalis (L.) Verdcourt’ was aimed at evaluating the efficacy of a new product made of pongamia oil - pongamia oil soap at different concentrations in combating the major pests of vegetable cowpea, viz., pod borers, pod bugs, leaf miner and aphids.